2019
DOI: 10.1111/1753-6405.12869
|View full text |Cite
|
Sign up to set email alerts
|

Potential sources of cessation support for high smoking prevalence groups: a qualitative study

Abstract: Objective This study aimed to: i) explore potential sources of cessation support as nominated by disadvantaged smokers; and ii) identify factors influencing decisions to use these sources. Methods Semi‐structured interviews were conducted with 84 smokers accessing community service organisations from the alcohol and other drugs, homeless, and mental health sectors. Transcripts were coded and thematically analysed. Results Doctors emerged as the most commonly recognised source of cessation support, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…health conditions, indicated that they preferred supported methods when discussing methods of support associated with past and future quit attempts. 10 In 2019, while using NRT (17%) and asking a doctor for help to quit (10%) were the most common assisted methods of attempting to quit by Australian smokers in the previous 12 months, 23% had tried to quit by 'going cold turkey'. 11 A 2015 report on current smokers with at least one quit attempt indicated that 38% had never used a supported method, whereas 54% had used NRT and 18% had used the Quitline at least once.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…health conditions, indicated that they preferred supported methods when discussing methods of support associated with past and future quit attempts. 10 In 2019, while using NRT (17%) and asking a doctor for help to quit (10%) were the most common assisted methods of attempting to quit by Australian smokers in the previous 12 months, 23% had tried to quit by 'going cold turkey'. 11 A 2015 report on current smokers with at least one quit attempt indicated that 38% had never used a supported method, whereas 54% had used NRT and 18% had used the Quitline at least once.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…15 Besides, doctors are regarded as sources of cessation support due to their recognized ability to provide practical and emotional support. 25 However, these assistance methods are limited by the time and space and rely on the physicianpatient connection, which might not entirely meet smokers' personalized needs, particularly their age, smoking frequency, willingness, and quitting stages. 26 Additionally, smokers may feel reluctant or ashamed to share their situations concerning their privacy and pressure from media or non-smokers.…”
Section: Related Workmentioning
confidence: 99%
“…The positive effects from emotional support on smoking cessation have been reported during traditional interventions, such as phone counselling [39]. In addition, anticipated emotional support has been deemed an important reason for smokers to use doctors, quit lines, and community service organization staffs, as such emotional support can help them with smoking cession performance [40]. Here, we assume that emotional support from smoking cessation OHCs will help smokers enhance their confidence in smoking cessation, as well as their smoking cessation performance.…”
Section: Research Hypothesesmentioning
confidence: 99%